PLANTS AS SOURCES OF HUMAN HEALTH PRODUCTS - Houghton, Peter (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plants continue to provide novel molecules for therapeutic use but also there is increasing interest in the acceptance of extracts or mixtures of plants in Western medicine. Examples of molecules achieving clinical importance in recent years are galantamine, huperzine A and artemisinin whilst other natural products are valuable as lead compounds. Many clinical trials are now being carried out on herbal products e.g. ginkgo, black cohosh, Job’s tears and some encouraging results are being obtained which substantiate their acceptance in mainstream Western medicine as well as in their traditional cultural environments. Regulatory systems are becoming more sympathetic but also recognising the need for good quality and adequate safety testing. Novel analytical and drug discovery approaches are consolidating the scientific appraisal of plants as sources of new medicines.